A Coherent Approach of Indexing Methods to Assess the Water Quality of River Bodies in Arrah, Bihar, India - Sardana, Mohita; Pandit, Dina Nath; Kuamri, Sangeeta; Kumari, Punam; Kumar, Om Prakash; Kumari, Mikki; Kumari, Sima; Alam, Md Noor (International Journal of Membrane Science and Technology, 2023)
Different river bodies are diverse sustaining systems that provide freshwater to rapidly growing needs at the domestic, agricultural and industrial levels of the people of India. The river bodies need periodical examination for conservation and rejuvenation because they are currently under stress due to pollution and climate change. Arrah is a district of Bihar, India and occupies an area of 2395 km2 for agriculture as the predominant activity. It is an attempt to assess the water quality of River Ganga, Sone and Gangi in this area by combining the overall pollution index (OPI), comprehensive pollution index (CPI) and water quality index (WQI) from November 2021 to October 2023 from 648 water samples and nine sampling sites to establish a relationship between any change in water quality and their sources. We assessed eleven water quality parameters following standard methods for winter, summer and monsoon seasons. Observations showed that dissolved oxygen, total alkalinity, fluoride and rarely biochemical oxygen demand exceeded Bureau of Indian Standards (BIS 2012) prescribed limits and indicated deterioration in the water quality of these river bodies. Two-way ANOVA suggested that the water quality parameters of these river bodies showed significant differences (p<0.05). We used Numerical equations to transform the concentration values into pollution indices. Values of OPI (1.70 to 2.40) and CPI (0.65 to 0.90) indicate acceptable/ slightly polluted/moderately polluted water in these rivers. Values of WQI of these river bodies ranged from 182.0-192.1, 220.1-242.2 and 190.7-238.9 during winter, summer and monsoon seasons, indicating poor/very-poor water quality. The observation shows that the causes of the declining water quality in these water bodies are anthropogenic activity, agricultural waste runoff and entry of untreated sewage. To reduce the time-consuming and expensive water quality monitoring and assessment programmes for these river bodies, the water quality of these water bodies felt the need to adopt proper management policies and conservation efforts.